Prevention, Management and Resolution of Political Conflicts in Nigeria: The Polite Language Approach - Nwabunze, Donatus Chijioke; Obi, Ngozi M. (South Asian Journal of Social Sciences and Humanities, 2020)
As it has been observed by Aristotle centuries ago, of all the animals on earth, humans are the only beings endowed with the capacity to talk. They can as well use and manipulate diverse tools for various purposes. But the most important tool that makes them unique from other animals is their capacity to make use of speech to interact. Man is language; language is man. As social beings’ people cannot get along in the society without it, as far as communication is concerned. However, apart from positive functions of language, it can also perform negative functions when used offensively. It can be used both as constructive and destructive tool. The world over, offensive language leads to conflict –serious disagreement, quarrel or dispute between one person and another, between two groups of people, and even between nations. Interestingly language can equally be used to prevent, control, manage or settle disputes. It is the view of this paper that global conflicts, with particular reference to Nigeria, can be prevented, controlled and managed if the citizens can learn to use language constructively in a manner that does not slur and smear others. This paper further argues that inter-personal, ethnic and national conflicts can be curbed in Nigeria with skillful application of polite language in any communication event. Conclusively, this paper is of the view that the avoidance of conflict-inducing language would enhance fellowship of Nigerian citizens, rather than fellowship of race, ethnicity, religion and class in the country. As an empirical study, the research has Brown and Levinson’s politeness theory, and Deborah Cameron’s verbal hygiene theory, as theoretical frameworks. It is hoped that the study will complement all the efforts government has been making in the prevention, management and resolution of various politically motivated conflicts which are threatening the corporate existence of Nigeria as a nation.